Stroke Care Within the COVID-19 Pandemic—Increasing Awareness of Transient and Mild Stroke Symptoms Needed - Uphaus, Timo; Gröschel, Sonja; Hayani, Eyad; Hahn, Marianne; Steffen, Falk; Gröschel, Klaus (Frontiers in Neurology, 2020)
Background: The COVID-19 pandemic might affect health care resources and alter patient admission to hospital in case of stroke or transient ischemic attack (TIA). We aim to determine whether the COVID-19 pandemic is affecting utilization of recanalization procedures and numbers of patients with stroke and TIA admitted to a primary care stroke center. Methods: In this retrospective observational study we, compared patients admitted from January 2019 until February 2020 with patients admitted during the COVID-19 pandemic (March/April 2020) in Germany. We included patients with stroke (hemorrhagic or ischemic) or TIA as classified by International Statistical Classification of Diseases and Related Health Problems version 10 (ICD-10). Results: The number of patients per month with ischemic strokeor TIA was found to have significantly decreased from January 2019 until February 2020 compared to the COVID-19 pandemic (March/April 2020) (ischemic stroke 69.1±4.5 vs. 55±5.7, p<0.001, TIA 22.1±4.1 vs. 14.5±6.4, p<0.034). Contrarily, percentages and numbers of recanalization procedures per month were not influenced by the COVID-19 pandemic (intravenous thrombolysis (iv-tPA) 9.4±3.7 vs. 10.5±0.5, p=0.697, mechanical thrombectomy (MT) 13.1±3.1 vs. 14.5±3.5, p=0.580, iv-TPA or MT 19.4±4.1 vs. 19.0±0.0, p=0.889). Conclusions: During the COVID-19 pandemic, resources of the healthcare system in a primary care University hospital in Germany still allowed for unchanged numbers of recanalization procedures due to ischemic stroke. However, the numbers of patients admitted to the hospital specifically due to ischemic stroke or TIA decreased, suggesting that the awareness for non-disabling stroke symptoms has to be increased.